A preterm neonate with fetal anemia and immune hydrops fetalis requiring intrauterine transfusion and postnatal exchange transfusion: a case report - Patel, Bhavya; Mehta, Abhijit; Shah, Binoy; Mehta, Ashish; Shah, Manish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Hydrops fetalis is a presenting illness with various immune and non-immune etiologies. It involves fluid accumulation in body cavities, and symptoms specific to its underlying cause. In this case, we report on a preterm neonate with a history of bad obstetrics who presented with hydrops fetalis due to fetal anemia related to RH incompatibility. The patient received an intrauterine transfusion for severe fetal anemia and subsequently required NICU admission. Routine preterm care was provided, along with specific management for jaundice resulting from isoimmune hemolytic anemia.